2019
DOI: 10.1111/coa.13404
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative plasma fibrinogen as a predictive factor for post‐tonsillectomy haemorrhage

Abstract: Objectives To assess whether preoperative plasma fibrinogen is able to predict severe post‐tonsillectomy haemorrhage. Study design Retrospective chart review. Methods We included 456 patients who underwent tonsillectomy between 2008 and 2013. Preoperative plasma fibrinogen levels (PFL) were assessed in patients who developed severe bleeding requiring surgical revision under general anesthesia compared to those with uneventful postoperative courses. Results 414 (90.8%) had no severe post‐tonsillectomy haemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
6
2
Order By: Relevance
“…In the present study, 2 type III events (4.2%) occurred on the control side (none on the device side). This percentage was lower than the rates reported in two larger studies, which showed 5.6% and 9.2% RTT events [4,20]. Currently, the use of this device has increased in the ENT community, which will generate larger data sets.…”
Section: Discussioncontrasting
confidence: 57%
“…In the present study, 2 type III events (4.2%) occurred on the control side (none on the device side). This percentage was lower than the rates reported in two larger studies, which showed 5.6% and 9.2% RTT events [4,20]. Currently, the use of this device has increased in the ENT community, which will generate larger data sets.…”
Section: Discussioncontrasting
confidence: 57%
“…14,15 Other authors consider elevated preoperative levels of plasma fibrinogen to be a significantly worse prognostic factor for post-tonsillectomy hemorrhage. 9…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the lymphocyte count (absolute, relative, neutrophile to lymphocyte ratio (NLR), and platelet to lymphocyte ratio (PLR)) has been studied in relation to different types of bleeding (GI tract bleeding, intracranial, cardiothoracic hemorrhage, post-tonsillectomy hemorrhage) 7,8 ; fibrinogen levels 9 and C-reactive protein levels 10,11 have been associated with the risk of post-tonsillar or upper or lower GI tract bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…However, wound infection, early intake of solid/hot food, and frequent coughing can induce pseudo-membrane instability and hemorrhage. 34 Some patients in this study underwent intraoperative suturing to close the wound in the tonsillar fossa with the aim of reducing wound exposure to food, infection risk, and postoperative pain. Previously published data in this cohort showed that intraoperative suture reduced secondary PTH incidence and PTH severity, with no patients in the suture group experiencing primary PTH.…”
Section: Discussionmentioning
confidence: 99%